Beyond Britain : Stuart Hall and the postcolonializing of Anglophone cultural studies - Jensen, Lars. (London : Rowman & Littlefield International, 2014)
"This book presents a history of the key ideas that have shaped the evolution of the shared spaces of inquiry in British Cultural Studies and Postcolonial Studies to analyse the continued significance and relevance of both disciplines beyond their British sites of origin"--Provided by publisher.
Introduction: The evolution of postcolonial studies and British cultural studies, and Stuart Hall -- National culture and the origins of British cultural studies -- Intellectual influences : Marxist debates and Commonwealth critiques -- Antonio Gramsci : bridging the gap between postcolonial studies and cultural studies -- Subaltern studies and cross cultural approaches -- Talking about the Caribbean : terminology, postcolonial theory and cultural studies -- Epilogue: The afterlife of Stuart Hall, cultural studies and postcolonial studies, in Britain and beyond -- Works cited.
Includes bibliographical references and index.
Keywords: Hall, Stuart, -- 1932-2014.; Great Britain -- Civilization -- Study and teaching; Postcolonialism -- Study and teaching; Great Britain -- Colonies -- Study and teaching; English-speaking countries -- Study and teaching; Great Britain -- Colonies -- Race relations -- Study and teaching